Chronic antidepressant potentiates spontaneous activity of dorsal raphe serotonergic neurons by decreasing GABAB receptor-mediated inhibition of L-type calcium channels. Issue 1 (December 2017) - Asaoka, Nozomi; Nishitani, Naoya; Kinoshita, Haruko; Kawai, Hiroyuki; Shibui, Norihiro; Nagayasu, Kazuki; Shirakawa, Hisashi; Nakagawa, Takayuki; Kaneko, Shuji
Abstract Spontaneous activity of serotonergic neurons of the dorsal raphe nucleus (DRN) regulates mood and motivational state. Potentiation of serotonergic function is one of the therapeutic strategies for treatment of various psychiatric disorders, such as major depression, panic disorder and obsessive-compulsive disorder. However, the control mechanisms of the serotonergic firing activity are still unknown. In this study, we examined the control mechanisms for serotonergic spontaneous activity and effects of chronic antidepressant administration on these mechanisms by using modifiedex vivo electrophysiological recording methods. Serotonergic neurons remained firing even in the absence of glutamatergic and GABAergic ionotropic inputs, while blockade of L-type voltage dependent Ca2+ channels (VDCCs) in serotonergic neurons decreased spontaneous firing activity. L-type VDCCs in serotonergic neurons received gamma-aminobutyric acid B (GABAB ) receptor-mediated inhibition, which maintained serotonergic slow spontaneous firing activity. Chronic administration of an antidepressant, citalopram, disinhibited the serotonergic spontaneous firing activity by weakening the GABAB receptor-mediated inhibition of L-type VDCCs in serotonergic neurons. Our results provide a new mechanism underlying the spontaneous serotonergic activity and new insights into the mechanism of action of antidepressants.